Cross - border partnerships and the issue of qualification conflicts: A German perspective - Reis, Dominik (Department of Commercial Law, 2014)
The ongoing process of economic globalization entails integration of national economies into the international economy and requires internationalization of national business structures. The progressing internationalization and globalization processes do however no longer only prompt the big concerns to operate on the world market. To an increasing extent smaller businesses also start to maintain international economic relations in order to resist the national and international competitive pressure and to represent marketability. Cross-border partnership structures are consequently increasingly common.